Cold-water coral mounds are effective carbon sinks in the western Mediterranean Sea - L. Greiffenhagen; J. Titschack; C. Wienberg; H. Wang; H. Wang; D. Hebbeln; D. Hebbeln (Biogeosciences)
Cold-water corals (CWCs) build biogenic structures, known as CWC mounds, that can store large amounts of carbon(ate). However, there is a lack of quantification studies on both recent as well as geological timescales, and knowledge is limited to the accumulation of carbonate (i.e. the inorganic carbon fraction), which ignores the organic carbon fraction. This hinders the calculation of total carbon accumulation rates and a wider understanding of the role CWC mounds play in the carbon cycle. Here, we investigated two cores retrieved from CWC mounds in the Alborán Sea, western Mediterranean Sea, comprising a ∼ 400 kyr record of carbon accumulation. We calculated the accumulation of both inorganic and organic carbon within the CWC mounds. Further, we analysed the same parameters in two cores from the adjacent seafloor (∼ 120 kyr record) to compare the mound records with the surrounding sedimentary deposits. Our results show that the CWC mounds studied accumulate up to 15 g C cm−2 kyr−1, of which 6 %–9 % is derived from the organic carbon fraction. Moreover, during mound formation phases, the mounds store up to 14–19 times more carbon than the adjacent seafloor deposits. We suggest that there is a selective enrichment of organic carbon on the mounds, with about an order of magnitude higher organic carbon accumulation rates than on the adjacent seafloor. Consequently, in phases of mound formation, CWC mounds can be effective local sinks of both inorganic and organic carbon on geological timescales.